Photoacoustic Microscopy in Tissue Engineering - Cai, Xin (2013)
Photoacoustic tomography (PAT) is an attractive modality for noninvasive, volumetric imaging of scattering media such as biological tissues. By choosing the ultrasonic detection frequency, PAT enables scalable spatial resolution with desired imaging depth up to ~7 cm while maintaining a high depth-to-resolution ratio of ~200 and consistent optical absorption contrasts. Photoacoustic microscopy (PAM), the microscopic embodiment of PAT, aims to image at millimeter depth and micrometer-scale resolution. PAM is well-suited for characterizing three-dimensional scaffold-based samples, including scaffolds themselves, cells, and blood vessels, both qualitatively and quantitatively. Here we review our previous work on applications of PAM in tissue engineering and then discuss its future developments.